Balanço hídrico e estimativa do consumo relativo de água da cultura de amoreira-preta em sistema orgânico para manejo automatizado de irrigação na região de Cascavel – Paraná - Feil, Ademar Cézar (2019)
This trial aims at determining the water balance and estimating the relative water consumption for blackberry crop (Rubus spp) in different phonologic phases, under organic system, in Cascavel municipality, to provide useful information to the farmers for irrigation management and to improve the plants development. The data applied in the study are based in 2018, and diary sequential water balance and dairy normal water balance were calculated, both, using 100 mm as soil water storage capacity (WSC). Water Requirement Satisfaction Index (WRSI), defined as the relation between actual evapotranspiration and crop evapotranspiration (ETr/ETc), was used as a criterion during the phenological phases favorable for blackberry cropping. The results have shown that the vegetative growth, flowering and fruits ripening phases were the most critical periods in relation to water deficit, considering the harvest from November to January, it is essential to replace water in these periods to prevent a decrease in productivity and decrease the productive potential of the next cycle.